2018
DOI: 10.1177/2158244018811406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Future School Counselors’ Competences for Inclusive Education

Abstract: The article discusses results of a study that evaluated university students' competencies related to inclusive education. The study aimed to find out how prospective school counselors, who were familiar with theories on inclusion as an educational concept and had some relevant field experience, analyzed and reflected upon inclusion-related, real-life situations. The authors also aimed to establish any differences in views and explanations depending on students' average grades and whether students have experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
5
Order By: Relevance
“…The process of internal state reflection can be influenced by various factors, from evaluation and supervision processes (Mažgon et al, 2018;Schofield & Grant, 2013) to research activities on the counseling process and itself to improve internally. In particular, supervision activities provide the chance for thorough reflection (Kernberg, 2019;Lysaker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The process of internal state reflection can be influenced by various factors, from evaluation and supervision processes (Mažgon et al, 2018;Schofield & Grant, 2013) to research activities on the counseling process and itself to improve internally. In particular, supervision activities provide the chance for thorough reflection (Kernberg, 2019;Lysaker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies in the literature, it has been concluded that teachers find themselves competent in inclusive practices. (Everington, Stevens, & Winters, 1999;Mirošević, 2016;Mažgon, Jeznik, & Ermenc, 2018;Şimşek, 2019;Akdal, Bozdağ, Aydın, & Aşkan, 2020;Dayı, Açıkgöz, & Elçi, 2020). The presence of information about inclusive education in the content of teacher training programs will contribute to the more qualified preservice teachers' training and to see themselves competent.…”
Section: Discussionmentioning
confidence: 99%
“…učiteljev z medkulturno zmožnostjo. Ključni so kakovostno izobraževanje in stališča, ki vplivajo na učiteljevo vedenje v razredu (Lesar 2007;Peček, Ermenc 2016;Mažgon, Jeznik, Ermenc 2018). Stališča predstavljajo pripravljenost posameznika za določeno ravnanje in usmerjajo njegove odnose in ravnanje v konkretnih učno-vzgojnih situacijah in so še zlasti pomembna pri odločanju, katero metodo ali postopek uporabiti, kadar postopki niso predpisani ali rutinski (Razdevšek Pučko 1990).…”
Section: Stališča Pedagoških Delavcev Kot Pogoj Udejanjanja Medkultur...unclassified